KOMUNIKASI VISUAL KARTUN SOMPRET KARYA I WAYAN SADHA - I Wayan Nuriarta; I Gede Agus Indram Bayu Artha; Ni Putu Dhea Pramesti; Pande Putu Sastra Wibawa (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
This paper was written to read visual signs and verbal markscontained in the cartoon Sompret by I Wayan Sadha. I Wayan Sadha'sSompret cartoon has its uniqueness as a work of visual communication.The uniqueness is that the visual communication of this cartoon presentsillustrations, typography, and layouts with a deep appreciation of Balineseculture. The illustration presents a Balinese wearing a headdress is arepresentation of a Balinese in traditional culture. The illustration of aBalinese without a headdress is a representation of a Balinese who is in themodern culture. The typography used utilizes the display font to presentthe conversation and clarify the description of the image. The letters areused to explain the issue raised as Sadha's opinion and point of view on theBali issues. Sadha's Sompret Cartoons only use lines, no color, so his worksappeared as black and white cartoons. Sompret cartoons used thesymmetrical balance composition and hidden balance layout, theperspective of human eye level, and the perspective of a bird's eye. Thisresearch uses descriptive qualitative research method. Semiotic theory isused in this research and focus on denotation and connotation meaning.Denotationally, the Sompret cartoon of Sadha presents a narrative ofevents based on the issue raised related to Balinese traditional culture andthe flow of globalization. The work is created in a one-panel cartoon. Thestory of this cartoon sometimes with conversations of several charactersor only illustrations of the characters without any conversation. With thenarrative being built, the meaning of the connotation can be read. Theconnotations meaning of Sompret cartoons as opinion cartoons is showingthe flow of globalization or modern culture in the middle of the strength ofthe Balinese traditional culture. Connotatively this cartoon can be read asa development of globalization in Bali